Effect of screen time on sleep quality among young adults: An observational cross-sectional study - Anjali Venkat; Mythri G; Anagha Avinash; Yuktha Hadly Devaraju (Asian Journal of Medical Sciences, 2025)
Background: Good sleep quality is associated with a wide range of positive outcomes, including better health, reduced daytime sleepiness, enhanced well-being, and improved psychological functioning. Over the past decade, the availability and usage of electronic devices have increased sharply, making them an integral part of young adults’ lives. Blue light radiation emitted from electronic devices is known to suppress the production of melatonin – a hormone essential for sleep initiation – thereby worsening sleep quality. Aims and Objectives: To assess the effect of screen time on sleep quality among young adults and determine which component of sleep quality is most affected. Materials and Methods: This cross-sectional study was conducted after obtaining permission from the Institutional Ethics Committee. A total of 437 participants aged 18–25 years participated in an online survey. Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI). Data were analyzed using SPSS 27. Results: The average PSQI score was 5.94 (PSQI ≥5 indicates poor sleep quality). A significant association was observed between longer screen time and higher PSQI scores. Sleep latency was the most significantly affected component in our study. Conclusion: A substantial proportion of young adults in our study experience poor sleep quality, which is strongly associated with increased screen time. Since sleep latency is the most affected component, limiting electronic device usage before bedtime could help improve sleep quality.